Building a Saudi Waqf Index: public data, Sharia governance, and policy design for a resilient endowment ecosystem - Hajed A. Alotaibi; Salem R. Alazizi (Humanities and Social Sciences Communications, 2026)
Abstract The concept of Waqf (Islamic endowment) has re-emerged as a key pillar in the institutional structure of social development and financial sustainability as part of Vision 2030 in Saudi Arabia. Empirical studies of the waqf sector, however, continue to face a measurement deficit: no single, publicly verifiable framework exists to systematically track its size, governance quality, and socioeconomic impact over time. This study addresses that gap by constructing a Saudi Waqf Index (SWI) for the 2018–2024 period, drawing exclusively on official annual reports published by the General Authority for Awqaf (GAA). The index operationalises four Sharia governance principles as quantifiable measurement constructs: Ḥifẓ al-māl (protection of wealth), amānah (fiduciary stewardship), bayān (transparency), and sharṭ al-wāqif (founder-stipulation compliance). These constructs are embedded within four analytical pillars: financial sustainability, ecosystem readiness, governance architecture, and social alignment. Using longitudinal, sector-level data from official government sources, the study traces indicative patterns of institutional consolidation across resource structure, regulatory convergence, sectoral allocation, and benefit distribution. Findings indicate steady institutionalisation and financial growth post-2018, alongside a persistent lag in outcome-based social impact measurement. The paper offers a reproducible, policy-relevant diagnostic framework for waqf assessment grounded in public data and Sharia-informed governance principles.